Tinjauan Terhadap Putusan Hakim Pada Pelaku Tindak Pidana Penistaan Agama Melalui Jejaring Sosial - Diki Dwi Laksono; Benny Irawan (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
The verdict in the case of Alnoldy Bahari Alias Ki Ngawur Permana Bin Altik Hanafi has raised concerns due to its perceived cultural unfairness, especially considering Pandeglang Regency's identity as a city with a significant Muslim population. This paper aims to scrutinize and analyze the judge's considerations in the case of blasphemy through social networks, specifically in the Banten High Court Decision Number: 26/PID /2018/PT. BTN. Additionally, it seeks to analyze the purpose of punishment for blasphemy through social networks according to the Electronic Information and Transaction Law. Conducted as normative legal research, this study employs a case study research approach with qualitative analysis of the obtained data. The findings emphasize the relevance of legal provisions, such as Article 45A paragraph (2) jo. Article 28 paragraph (2) of Law No. 19 of 2016, which amends Law No. 11 of 2008 concerning Electronic Information and Transactions, in conjunction with Article 64 paragraph (1) of the Criminal Code. The impact of the case on the social fabric of the Pandeglang Regency community is considered, stressing the importance of crime prevention and prosecution strategies within the framework of criminal law. Furthermore, the study underscores the role of punishment in acting as a deterrent for future offenses and as a mechanism for judicial control, ensuring clarity and effectiveness in the application of penalties.